Nickel-based single crystal hydroxide precursor, positive electrode material, preparation method of positive electrode material, positive electrode and battery

Nickel-based single-crystal hydroxide precursors were prepared through the coordinated regulation technology of hierarchical nucleation-ripening-growth, which solved the structural instability problem of high-nickel ternary positive electrode materials and achieved the preparation of high-performance single-crystal positive electrode materials with high specific capacity and excellent electrochemical properties, simplified the process and reduced energy consumption.

CN120622567APending Publication Date: 2025-09-12YIBIN LIBODE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510830944.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

Existing high-nickel ternary positive electrode materials have poor electrochemical performance and insufficient safety performance due to structural instability and thermodynamic instability, making them difficult to apply on a large scale. Especially in the high-temperature, high-lithium ratio sintering process, the traditional preparation method is complex and the performance of the obtained single crystal positive electrode materials is insufficient.

Method used

Nickel-based single-crystalline hydroxide precursors are prepared using a synergistic control technology of staged nucleation-ripening-growth. By controlling the reaction conditions and feeding method, single-crystalline precursors with regular morphology, micro-nano scale, and high dispersion are obtained, avoiding high-temperature and high-lithium ratio sintering, and preparing single-crystalline positive electrode materials with few or no defects.

Benefits of technology

A highly dispersed, regular-morphology single-crystal positive electrode material has been achieved, which has high specific capacity, excellent rate performance and reversibility, simplifies the preparation process, reduces energy consumption, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622567A_ABST
    Figure CN120622567A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, and discloses a nickel-based single crystal hydroxide precursor, a positive electrode material, a preparation method of the positive electrode material, a positive electrode and a battery. The disclosed precursor is a primary particle, the D50 is 1-5 [mu] m, and the specific surface area is less than 10 m < 2 > / g. The preparation method comprises the following steps: enabling a mixed metal salt solution, an alkali solution and ammonia water to flow into a reaction kettle in parallel, controlling the pH value of the reaction kettle to be 12.5-13.0, maintaining the ammonia concentration to be 1.5-2.5 mol / L, and maintaining for 20-60 minutes; stopping feeding, and keeping for 20 to 60 minutes; circulating the process for 3-10 times; feeding of the mixed metal salt solution is stopped, the pH is adjusted to be 10.5-11.5, the ammonia concentration is adjusted to be 1.5-2.5 mol / L, and all feeding is stopped after the target particle size is reached. The precursor is a true single crystal material and has regular morphology, relatively good size and relatively good dispersity, and the positive electrode material prepared from the precursor has relatively good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a nickel-based single crystal hydroxide precursor and a positive electrode material and a preparation method thereof, a positive electrode and a battery. Background Art

[0002] High-nickel ternary cathode materials, as crucial components in lithium-ion batteries, have attracted considerable attention due to their unique advantages in energy density and cycling stability. However, the widespread application of high-nickel (Ni ≥ 80%) ternary cathode materials, particularly ultra-high-nickel (Ni > 90%) cathode materials, is severely hampered by structural and thermodynamic instability, resulting in poor electrochemical performance and insufficient safety. Large-grained polycrystalline spherical structures and single-crystal structures are the two most common particle structures in high-nickel cathode materials. Large-grained polycrystalline spherical particles are formed by the agglomeration of anisotropic primary nanocrystalline single-crystal particles, approximately 3 to 20 μm in size, exhibiting excellent flowability and a low specific surface area. However, secondary particles, aggregated by intermolecular forces, are susceptible to breakage during the electrode roll pressing process. Furthermore, the disordered volume effects of the anisotropic primary particles during charge-discharge cycling lead to the generation and propagation of intergranular and lattice cracks, exacerbating surface and interfacial side reactions and significantly reducing the volumetric energy density, structural stability, and thermal stability of large-grained polycrystalline layered nickel-based oxide cathode materials. This is also a major problem facing current commercial polycrystalline and agglomerated positive electrode materials.

[0003] The single crystal particle structure can improve the material structure stability and effectively solve the above-mentioned problems of polycrystalline structure materials. The particle structure of the nickel-based hydroxide precursor directly affects the sintering process of the single crystal high nickel positive electrode material. The applicant found in the previous research on the synthesis of single crystal NCA positive electrode materials that Ni 0.8 Co 0.15 Al 0.05 The particle size and specific surface area of ​​the (OH)2 precursor determine the size and electrochemical properties of the single crystal finished material. Small particle size (3-5 μm), high specific surface area (~40 m 2 Due to its high reactivity, a precursor with a small particle size and high specific surface area can be used to prepare a monodisperse single-crystalline NCA cathode material at a sintering temperature of 800°C and a lithium ratio of 1.15. Its volumetric energy density and electrochemical stability are far superior to those of large-particle polycrystalline spherical structures [Journal of Alloys and Compounds, 2017, 695:9199]. However, the use of this small-particle, high-specific-surface-area precursor to construct single-crystalline high-nickel cathode materials still requires high-temperature sintering and a high lithium ratio, and the resulting single-crystalline cathode materials still lack reversibility, rate capability, and cycling performance.

[0004] To address this issue, the preparation method of large-grained single-crystal lithium-ion battery ternary positive electrode material disclosed in CN109286016A in 2018 uses a polycrystalline precursor as the precursor, which requires wet mixing and drying before sintering, and needs to be sintered in a rotary furnace. The process is complicated, and the single-crystal ternary material prepared by this method has irregular particle morphology and is too large in size, which is not conducive to the performance of the material. In the preparation method of high-nickel ternary single-crystal material precursor disclosed in CN114436346A in 2022, a single-crystal morphology precursor material is obtained by sintering inorganic and organic dispersants in a coprecipitation process, but this process requires the addition of additional dispersants and requires ethanol solution to wash impurities. The resulting single-crystal precursor material is prone to agglomeration. In 2022, Kunming University of Science and Technology disclosed a method for preparing a single-crystal high-nickel positive electrode material, CN115028210B, which uses an ammonia complexation-boiling precipitation method to prepare a single-crystal doped nickel hydroxide precursor with larger primary particles. This avoids the harsh conditions such as high temperature and high lithium ratio involved in the preparation of traditional single-crystal positive electrode materials, as well as complicated processes such as water washing. However, the precursor obtained by this method is a spherical / quasi-spherical shape agglomerated from large flaky primary particles. The obtained single-crystal positive electrode material still needs to be crushed and graded, and the reaction rate in the boiling state is too fast to be controllable. The operation is difficult, and the volatilization of ammonia is difficult to control. Therefore, in order to achieve performance improvement and large-scale application of ultra-high specific capacity and high-rate nickel-based layered oxide positive electrode materials, it is urgent to develop highly dispersed single-crystal precursors and controllable preparation technologies thereof.

[0005] In view of this, the present invention is proposed. Summary of the Invention

[0006] The object of the present invention is to provide a nickel-based single crystal hydroxide precursor and a positive electrode material and a preparation method thereof, a positive electrode and a battery, aiming to improve at least one problem mentioned in the background art.

[0007] The present invention is achieved in that:

[0008] In the first aspect, the present invention provides a nickel-based single crystal hydroxide precursor, the chemical formula of which is Ni 1-x-y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3;

[0009] The precursor is a primary particle with a D50 of 1 to 5 μm, a single crystal primary particle size range of 0.2 to 2 μm, and a polyhedral morphology.

[0010] In an optional embodiment, the polyhedron is a prismatic cubic polyhedron, the prism side aspect ratio is (1-5):1, and the specific surface area is less than 10m 2 / g.

[0011] In a second aspect, an embodiment of the present invention provides a method for preparing the aforementioned precursor, comprising:

[0012] Stepwise nucleation:

[0013] Nucleation: The mixed metal salt solution, alkaline solution and ammonia water are introduced into the reactor in parallel, the pH of the reactor is controlled at 12.5-13.0, and the ammonia concentration is maintained at 1.5-2.5 mol / L for 20-60 minutes;

[0014] Maturation: Stop feeding the mixed metal salt solution, alkali solution and ammonia solution, and keep it for 20 to 60 minutes;

[0015] The nucleation-ripening step is repeated 3 to 10 times to complete the staged nucleation;

[0016] Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia solution feed to make the solution pH 10.5-11.5, and maintain the ammonia concentration at 1.5-2.5 mol / L. Keep it for 20-100 hours until the target particle size is reached, then stop all feeding;

[0017] The slurry is aged for 0.5 to 2 hours;

[0018] The temperature of the entire reaction process is 60-90°C.

[0019] In an optional embodiment, the preparation method includes at least one of the following features (1) to (4):

[0020] (1) The bottom liquid in the reactor accounts for 50-60% of the reactor volume, the ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0;

[0021] (2) The concentration of metal ions in the mixed metal salt solution is 1 to 2 mol / L, and during the nucleation process, the injection flow rate of the mixed metal salt solution is 10 mL / min to 2 L / min;

[0022] (3) After the aging is completed, the precipitate is extracted from the slurry, washed with an alkaline solution at a temperature of 60 to 90° C. and deionized water in sequence until the pH value of the precipitate is lower than 10, and then dried to obtain a precursor;

[0023] (4) The concentration of the ammonia water is 10-14 mol / L; the alkaline solution is a sodium hydroxide solution with a concentration of 8-10 mol / L.

[0024] In an optional embodiment, the flow rate of the ammonia solution is 5 mL / min to 1 L / min, and the flow rate of the sodium hydroxide solution is 5 mL / min to 1 L / min.

[0025] In a third aspect, an embodiment of the present invention provides a method for preparing a positive electrode material, comprising mixing and sintering the lithium source and the aforementioned precursor, wherein the molar ratio of lithium in the lithium source to the metal in the precursor is 1:1.01-1.05.

[0026] In an optional embodiment, the sintering conditions are: keeping the temperature at 400-500° C. for 2-6 hours in an oxygen atmosphere, then heating to 680-750° C. for 8-15 hours.

[0027] In a fourth aspect, the present invention provides a positive electrode material prepared by the preparation method as described in the aforementioned embodiment.

[0028] In a fifth aspect, the present invention provides a positive electrode, comprising the positive electrode material according to the aforementioned embodiment or the positive electrode material prepared by the preparation method according to the aforementioned embodiment.

[0029] In a sixth aspect, the present invention provides a battery comprising the positive electrode according to the aforementioned embodiment.

[0030] The present invention has the following beneficial effects:

[0031] The nickel-based single crystal hydroxide precursor provided by the present invention is a true single crystal material with a regular morphology, better size, and better dispersibility. The positive electrode material prepared using it does not need to be crushed or graded after sintering. The prepared positive electrode material can inherit the crystal structure of the single crystal precursor, has a lithium storage structure with few defects or no defects, and has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0032] The preparation method provided by the present invention develops a new single crystal precursor preparation technology with coordinated nucleation-ripening-growth regulation. The agglomeration of amorphous nanocrystalline nuclei is greatly reduced through the staged feeding nucleation technology, and micro-nano scale, highly dispersed, and preliminarily matured nickel-based single crystal hydroxide nuclei are prepared. The crystal growth is coordinated and controlled to achieve the controllable preparation of highly dispersed, large single crystal hydroxide precursors. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without paying any creative work.

[0034] Figures 1 to 5 The following are SEM images of the precursors prepared in Example 1 to Example 5 respectively;

[0035] Figures 6 to 10 The XRD patterns of the precursors prepared in Example 6 to Example 10 are respectively;

[0036] Figure 11 This is the SEM image of the positive electrode material prepared in Example 3. DETAILED DESCRIPTION

[0037] To make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer are used. Where the manufacturer of the reagents or instruments is not specified, all are conventional products that can be purchased commercially.

[0038] The features and performance of the present invention are further described in detail below with reference to the embodiments.

[0039] The embodiment of the present invention provides a nickel-based single crystal hydroxide precursor, the chemical formula of which is Ni 1-x- y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3;

[0040] The precursor is a primary particle with a D50 of 1 to 5 μm, a single crystal primary particle size range of 0.2 to 2 μm, and a polyhedral morphology.

[0041] The nickel-based single crystal hydroxide precursor provided in the embodiment of the present invention is a true single crystal material with a regular morphology, better size, and better dispersibility. It does not require crushing or grading after sintering to prepare the positive electrode material. The prepared positive electrode material can inherit the crystal structure of the single crystal precursor, has a lithium storage structure with few defects or no defects, and has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0042] Optionally, the polyhedral structure of the precursor is a prismatic cubic polyhedron, the prism side aspect ratio is (1-5):1, and the specific surface area is less than 10m 2 / g.

[0043] The method for preparing a precursor provided by an embodiment of the present invention comprises:

[0044] Stepwise nucleation:

[0045] Nucleation: The mixed metal salt solution, alkaline solution and ammonia water are introduced into the reactor in parallel, the pH of the reactor is controlled at 12.5-13.0, and the ammonia concentration is maintained at 1.5-2.5 mol / L for 20-60 minutes;

[0046] Maturation: Stop feeding the mixed metal salt solution, alkali solution and ammonia solution, and keep it for 20 to 60 minutes;

[0047] The nucleation-ripening step is repeated 3 to 10 times to complete the staged nucleation;

[0048] Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia solution feed to make the solution pH 10.5-11.5, and maintain the ammonia concentration at 1.5-2.5 mol / L. Keep it for 20-100 hours until the target particle size is reached, then stop all feeding;

[0049] The slurry is aged for 0.5 to 2 hours;

[0050] The temperature of the entire reaction process is 60-90°C.

[0051] The preparation method provided by the present invention develops a new single crystal precursor preparation technology with coordinated nucleation-ripening-growth regulation. The agglomeration of amorphous nanocrystalline nuclei is greatly reduced through the staged feeding nucleation technology, and micro-nanoscale, highly dispersed, and preliminarily matured nickel-based single crystal hydroxide nuclei are prepared. The crystal growth is coordinated to control the highly dispersed and large single crystal hydroxide precursors to be controllable. The D50 of the single crystal precursor primary particles prepared by this method is controllable in the range of 1 to 5 μm, the particle size distribution is uniform, the dispersion is high, the crystal structure is controllable, the process is simple, and no additional dispersant is required. The single crystal precursor has uniform morphology, good product consistency, and can be produced on a large scale. Applying it to the synthesis of single crystal positive electrode materials can avoid the shortcomings of traditional methods such as high lithium content and high-temperature calcination, thereby saving energy and reducing consumption from the root, and achieving green economy. The positive electrode material prepared from the precursor inherits the crystal structure characteristics of the single crystal precursor, has a lithium storage structure with few defects or no defects, and has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0052] Specifically, the preparation method is:

[0053] S1. Prepare base solution

[0054] Deionized water, ammonia water and sodium hydroxide solution are introduced into the reactor so that the bottom liquid in the reactor accounts for 50-60% of the volume of the reactor, the ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0.

[0055] S2, staged nucleation

[0056] Nucleation: Control the temperature in the reactor to 60-90°C, introduce an inert gas (such as nitrogen or argon) into the reactor, and then introduce a mixed metal salt solution, ammonia water, and an alkaline solution into the reactor in parallel. During the entire process, the pH of the reactor is controlled to be 12.5-13.0, and the ammonia concentration is maintained at 1.5-2.5 mol / L for 20-60 minutes.

[0057] Maturation, stop feeding, keep for 20 to 60 minutes;

[0058] The nucleation-ripening steps are cycled 3 to 10 times.

[0059] In this step, micro-nano scale, highly dispersed, and preliminarily matured nickel-based single crystal hydroxide nuclei are prepared under high pH conditions; then, the pH value is lowered to the nucleus growth point to allow the single crystal nuclei to grow slowly, and the nucleation-maturation steps are cyclically repeated to obtain a micron-scale nickel-based single crystal hydroxide precursor.

[0060] Optionally, the mixed metal salt solution contains nickel ions, and may contain manganese ions and cobalt ions; the types and ratios of the metal ions are determined according to the chemical formula of the precursor to be prepared.

[0061] Optionally, the salt used to prepare the mixed metal salt solution may be a salt currently disclosed to be used for preparing a precursor, such as a sulfate, specifically NiSO4.6H2O, CoSO4.7H2O, or MnSO4.H2O.

[0062] Optionally, the concentration of metal ions in the mixed metal salt solution is 1 to 2 mol / L, and during the nucleation process, the injection flow rate of the mixed metal salt solution is 10 mL / min to 2 L / min;

[0063] Optionally, the concentration of ammonia water is 10 to 14 mol / L, and the flow rate of ammonia water is dynamically controlled in the range of 5 mL / min to 1 L / min during the entire process to ensure that the ammonia value and pH value are within the required range; the alkaline solution is sodium hydroxide solution with a concentration of 8 to 10 mol / L, and the flow rate of sodium hydroxide solution is dynamically controlled in the range of 5 mL / min to 1 L / min during the entire process to ensure that the pH value is within the required range.

[0064] Optionally, the nucleation and aging processes are carried out under continuous stirring at a stirring speed of 500 to 900 rpm.

[0065] S3. Growth

[0066] Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia water feed to make the solution pH 10.5-11.5, maintain the ammonia concentration at 1.5-2.5 mol / L, and stop all feeding after maintaining the target particle size for 20-100 hours.

[0067] Optionally, the growth stage is carried out under constant stirring at a stirring speed of 500 to 900 rpm.

[0068] During the growth stage, lowering the pH value promotes the rapid growth of grains along the dominant crystal planes, allowing the particles to grow to the target size.

[0069] S4. Aging

[0070] After the growth stage, the slurry is aged for 0.5 to 2 hours to allow the solution system to stabilize and the transition metal to fully precipitate.

[0071] S5. Extraction of precursors

[0072] The aged slurry is filtered, and then the filter material is washed in sequence with a sodium hydroxide solution and deionized water at a temperature of 60-90°C and a mass fraction of 5%, until the pH value of the filtered filtrate after washing is lower than 10, indicating that the cleaning is completed. After the washed slurry is solid-liquid separated, it is placed in a forced air drying oven at 100-150°C and dried for 10-20 hours to obtain a true single crystal high nickel-based precursor with good particle size, good morphology and good dispersion uniformity.

[0073] The embodiment of the present invention provides a positive electrode material, the chemical formula of which is LiNi 1-x-y Co x Mn y O2, where 0≤x≤0.2, 0≤y≤0.2;

[0074] The precursor is a primary particle with a D50 of 1 to 5 μm, a single crystal primary particle size range of 0.2 to 2 μm, and a polyhedron morphology. The polyhedron is a prismatic cubic polyhedron with a prism side aspect ratio of (1 to 5): 1 and a specific surface area of ​​<10m 2 / g.

[0075] The positive electrode material is a true single crystal material with better size, better dispersibility, and a lithium storage structure with few or no defects. It has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0076] An embodiment of the present invention provides a method for preparing a positive electrode material, comprising mixing and sintering a lithium source and a precursor provided by an embodiment of the present invention, wherein the molar ratio of lithium in the lithium source to metal in the precursor is 1:1.01-1.05.

[0077] Optionally, the lithium source is at least one of lithium carbonate and lithium hydroxide.

[0078] Specifically, the sintering conditions are: keeping the temperature at 400-500° C. for 2-6 hours in an oxygen atmosphere, then heating to 680-750° C. for 8-15 hours.

[0079] Because the cathode material is prepared using the precursors produced in accordance with the present invention, the sintering temperature is low (less than 800°C), avoiding crystal defects caused by recrystallization. The resulting true single-crystal high-nickel cathode material perfectly inherits the crystal structure of the single-crystal precursor, possessing a lithium storage structure characterized by few or no defects, and exhibiting advantages such as high specific capacity, good rate performance, and excellent reversibility.

[0080] The positive electrode provided by the embodiment of the present invention includes the positive electrode material provided by the present invention.

[0081] The battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.

[0082] Example 1

[0083] This embodiment provides a nickel-based single crystal hydroxide precursor, a single crystal positive electrode material, and a preparation method thereof.

[0084] The chemical formula of nickel-based single crystal hydroxide precursor is LiNi 0.89 Co 0.07 Mn 0.04 (OH)2;

[0085] The molecular formula of the single crystal positive electrode material is LiNi 0.89 Co 0.07 Mn 0.04 O2;

[0086] The preparation method of the precursor is as follows:

[0087] Step 1: NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O according to n(Ni 2+ ):n(Co 2+ ): n(Mn 2+ )=89:7:4 are evenly mixed to prepare a metal salt mixed solution with a total concentration of 2 mol / L; a sodium hydroxide solution with a concentration of 10 mol / L is prepared; and an ammonia solution with a concentration of 10 mol / L is prepared.

[0088] In a 100L reactor, 45L of deionized water and 11L of ammonia water were added as the base liquid in advance, and an appropriate amount of sodium hydroxide solution was added to control the pH value of the base liquid to 12.5 (±0.05). The ammonia concentration in the base liquid was 2 mol / L. After the reaction was completely sealed and the air tightness was tested, nitrogen gas (0.2m 3 / h) to completely replace the oxygen in the reactor with the protective gas. When the temperature in the reactor reaches 80°C, the metal salt mixed solution, sodium hydroxide solution, and ammonia water are pumped into the reactor at flow rates of 40mL / min, 16mL / min, and 16mL / min, respectively, and the stirring speed is controlled at 800r / min. By adjusting the flow rate of sodium hydroxide solution and ammonia water, the pH value of the entire reactor was maintained at 12.5 (± 0.05) and the ammonia concentration was maintained at 2 (± 0.05) mol / L. The nucleation was carried out in stages for 8 hours (including 4 cycles, each nucleation was 60 minutes, and the aging was 60 minutes). After the reaction was completed, the flow rate of the alkaline solution was reduced to slowly reduce the pH of the solution in the reactor to 10.50 (± 0.05). The ammonia concentration remained unchanged and the reaction was continued for 20 hours. All feeding was stopped. After the slurry was aged for 30 minutes, the mother liquor was filtered and washed with 60°C alkaline solution (5% sodium hydroxide solution) for 30 minutes, and then washed with 60°C deionized water until the pH was below 10. It was then filtered and placed in a 100°C forced drying oven for 20 hours. Ni was obtained. 0.89 Co 0.07 Mn 0.04 (OH)2 precursor sample, its SEM image is shown in Figure 1 , D50 is 3.8μm, the single crystal primary particle size range is 0.3~1.0μm, the single crystal morphology is polyhedron, the single crystal is a prismatic cubic polyhedron, the prism side aspect ratio is (1~5):1, and the specific surface area is 3.4m 2 / g.

[0089] The preparation method of the positive electrode material is as follows:

[0090] Step 2: The precursor prepared in step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 for 60 minutes to ensure uniform mixing. The mixture was then placed in a tube furnace for high-temperature sintering under oxygen-rich conditions. The heating rate was controlled at 3°C / min; the temperature was raised to 450°C and kept at this temperature for 3 hours, then continued to rise to 750°C and kept at this temperature for 12 hours. The mixture was then cooled naturally to room temperature, and the sample was removed and ground to obtain the single crystal positive electrode material LiNi. 0.89 Co 0.07 Mn 0.04 O2.

[0091] Currently, the sintering temperature of single crystal positive electrode materials with a nickel-cobalt-manganese ratio of 0.89:0.07:0.04 is generally 800°C. The calcination temperature in this embodiment is 750°C, which is 50°C lower than the prior art, saving energy consumption.

[0092] Example 2

[0093] This embodiment provides a nickel-based single crystal hydroxide precursor, a single crystal positive electrode material, and a preparation method thereof.

[0094] The chemical formula of nickel-based single crystal hydroxide precursor is LiNi 0.92 Co 0.05 Mn 0.03 (OH)2;

[0095] The molecular formula of the single crystal positive electrode material is LiNi 0.92 Co 0.05 Mn 0.03 O2;

[0096] The preparation method of the precursor is as follows:

[0097] Step 1: NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O according to n(Ni 2+ ):n(Co 2+ ): n(Mn 2+ )=92:5:3 and evenly mix to prepare a metal salt mixed solution with a total concentration of 1.5 mol / L; prepare a sodium hydroxide solution with a concentration of 10 mol / L; prepare ammonia water with a concentration of 14 mol / L.

[0098] In a 100L reactor, 50L of deionized water and 6L of ammonia water were added as the bottom liquid in advance, and the pH value of the bottom liquid was controlled to 12.7 (±0.05) with sodium hydroxide solution, and the ammonia concentration was 1.5mol / L. After the reaction was completely sealed and the airtightness was tested, nitrogen gas (0.2m 3 / h) so that the protective gas completely replaces the oxygen in the reactor. When the temperature in the reactor reaches 70°C. The metal salt mixed solution, sodium hydroxide solution and ammonia water are pumped into the reactor at flow rates of 80mL / min, 24mL / min and 20mL / min respectively, and the stirring speed is controlled at 800r / min. The pH value of the entire reactor is maintained at 12.7 (±0.05) and the ammonia concentration is maintained at 1.5 (±0.05) mol / L by adjusting the flow rates of sodium hydroxide solution and ammonia water. The step-by-step feeding and nucleation are carried out for 5h (a total of 5 cycles, each nucleation is 30min, and the maturation is 30min). After the reaction is completed, the flow rate of the alkaline solution is reduced to slowly reduce the pH of the solution in the reactor to 11.30 (±0.05), and the reaction is continued for 80h. After the reaction is completed, the slurry is aged for 1h, and then washed, filtered and dried in the same manner as in Example 1 above. LiNi is obtained. 0.92 Co 0.05 Mn 0.03 (OH)2 precursor sample, its SEM image is shown in Figure 2 , D50 is 2.8μm, the single crystal primary particle size range is 0.2~0.8μm, the single crystal morphology is polyhedron, the single crystal is a prismatic cubic polyhedron, the prism side aspect ratio is (1~5):1, and the specific surface area is 5.6m 2 / g.

[0099] Step 2: The precursor prepared in step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.03 for 60 minutes to ensure uniform mixing. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-rich conditions. The heating rate was controlled at 3°C / min; the temperature was raised to 480°C and kept at this temperature for 4 hours, then continued to rise to 720°C and kept at this temperature for 12 hours. The mixture was then cooled naturally to room temperature, and the sample was taken out and ground to obtain the single crystal positive electrode material LiNi. 0.92 Co 0.05 Mn 0.03 O2.

[0100] Currently, the sintering temperature of single crystal positive electrode materials with a nickel-cobalt-manganese ratio of 0.92:0.05:0.03 is generally 780°C. The calcination temperature in this embodiment is 720°C, which is 60°C lower than the prior art, saving energy consumption.

[0101] Example 3

[0102] This embodiment provides a nickel-based single crystal hydroxide precursor, a single crystal positive electrode material, and a preparation method thereof.

[0103] The chemical formula of nickel-based single crystal hydroxide precursor is LiNi 0.92 Co 0.05 Mn 0.03 (OH)2;

[0104] The molecular formula of the single crystal positive electrode material is LiNi 0.92 Co 0.05 Mn 0.03 O2;

[0105] The preparation method of the precursor is as follows:

[0106] Step 1: Prepare the same metal salt mixed solution, sodium hydroxide solution and ammonia water as in Example 2. In a 100L reactor, add 45L of deionized water and 10L of ammonia water as the base liquid in advance, and control the pH value of the base liquid to 12.5 (±0.05) with sodium hydroxide solution, and the ammonia concentration to 2.5mol / L. After the reactor is completely sealed and tested for airtightness, nitrogen gas (0.2m 3 / h) so that the protective gas completely replaces the oxygen in the reactor. When the temperature in the reactor reaches 80°C. The metal salt mixed solution, sodium hydroxide solution and ammonia water are pumped into the reactor at a flow rate of 80mL / min, 24mL / min and 24mL / min respectively, and the stirring speed is controlled at 700r / min. The pH value of the entire reactor is maintained at 12.5 (±0.05) and the ammonia concentration is maintained at 2.5 (±0.05) mol / L by adjusting the flow rate of sodium hydroxide solution and ammonia water. The step-by-step feeding and nucleation are carried out for 3h (a total of 3 cycles, each nucleation is 30min, and maturation is 30min). After the reaction is completed, the alkali solution feeding is stopped to reduce the pH of the solution in the reactor to 10.8 (±0.05). The reaction is continued for 100h. After the reaction is completed, the slurry is aged for 1h, and then washed, filtered and dried in the same manner as in Example 1 above. LiNi is obtained. 0.92 Co 0.05 Mn 0.03 (OH)2 precursor samples such as Figure 3 As shown, D50 is 4.2 μm, the single crystal primary particle size range is 0.6-2.0 μm, the single crystal morphology is polyhedron, the single crystal is a prismatic cubic polyhedron, the prism side aspect ratio is (1-5): 1, and the specific surface area is 2.9 m 2 / g.

[0107] Step 2: The precursor prepared in step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 for 60 minutes to ensure uniform mixing. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-rich conditions. The heating rate was controlled at 3°C / min; the temperature was raised to 450°C and kept at this temperature for 4 hours, then continued to rise to 720°C and kept at this temperature for 12 hours. The sample was then naturally cooled to room temperature and ground to obtain the single crystal positive electrode material LiNi. 0.92 Co 0.05 Mn 0.03 O2.

[0108] Currently, the sintering temperature of single crystal positive electrode materials with a nickel-cobalt-manganese ratio of 0.92:0.05:0.03 is generally 780°C. The calcination temperature in this embodiment is 720°C, which is 60°C lower than the prior art, saving energy consumption.

[0109] Example 4

[0110] This embodiment provides a nickel-based single crystal hydroxide precursor, a single crystal positive electrode material, and a preparation method thereof.

[0111] The chemical formula of nickel-based single crystal hydroxide precursor is LiNi 0.94 Co 0.05 Mn 0.01 (OH)2;

[0112] The molecular formula of the single crystal positive electrode material is LiNi 0.94 Co 0.05 Mn 0.01 O2;

[0113] The preparation method of the precursor is as follows:

[0114] Step 1: NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O according to n(Ni 2+ ):n(Co 2+ ): n(Mn 2+ )=94:5:1 and evenly mix to prepare a metal salt mixed solution with a total concentration of 2 mol / L; prepare a sodium hydroxide solution with a concentration of 10 mol / L; prepare an ammonia water with a concentration of 14 mol / L.

[0115] In a 100L reactor, 50L of deionized water and 8L of ammonia water were added as the bottom liquid in advance, and the pH value of the bottom liquid was controlled to 12.6 (±0.10) with sodium hydroxide solution, and the ammonia concentration was 2.0mol / L. After the reaction was completely sealed and tested for airtightness, nitrogen gas (0.2m 3 / h) so that the protective gas completely replaces the oxygen in the reactor. When the temperature in the reactor reaches 70°C. The metal salt mixed solution, sodium hydroxide solution and ammonia water are pumped into the reactor at flow rates of 80mL / min, 32mL / min and 32mL / min respectively, and the stirring speed is controlled at 600r / min. The pH value of the entire reactor is maintained at 12.6 (±0.05) and the ammonia concentration is maintained at 2.0 (±0.05) mol / L by adjusting the flow rates of sodium hydroxide solution and ammonia water. The feed is stepped and nucleated for 5h (a total of 6 cycles, each nucleation is 25min, and maturation is 25min). After the reaction is completed, the alkali solution feed is stopped to reduce the pH of the solution in the reactor to 11.1 (±0.05), and the reaction is continued for 80h. After the reaction is completed, the slurry is aged for 2h, and then washed, filtered and dried in the same manner as in Example 1 above. Ni is obtained. 0.94 Co 0.05 Mn 0.01 (OH)2 precursor samples, such as Figure 4 As shown, D50 is 5.0 μm, the single crystal primary particle size range is 1.0-2.0 μm, the single crystal morphology is polyhedron, the single crystal is a prismatic cubic polyhedron, the prism side aspect ratio is (1-5): 1, and the specific surface area is 4.7 m 2 / g.

[0116] Step 2: The precursor prepared in step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.03 for 60 minutes to ensure uniform mixing. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-rich conditions. The heating rate was controlled at 3°C / min; the temperature was raised to 450°C and kept at this temperature for 4 hours, then continued to rise to 700°C and kept at this temperature for 12 hours. The mixture was then cooled naturally to room temperature, and the sample was removed and ground to obtain the single crystal positive electrode material LiNi. 0.94 Co 0.05 Mn 0.01 O2.

[0117] Currently, the sintering temperature of single crystal positive electrode materials with a nickel-cobalt-manganese ratio of 0.94:0.05:0.01 is generally 760°C. The calcination temperature in this embodiment is 700°C, which is 60°C lower than the prior art, saving energy consumption.

[0118] Example 5

[0119] This embodiment provides a nickel-based single crystal hydroxide precursor, a single crystal positive electrode material, and a preparation method thereof.

[0120] The chemical formula of nickel-based single crystal hydroxide precursor is LiNi 0.94 Co 0.05 Mn 0.01 (OH)2;

[0121] The molecular formula of the single crystal positive electrode material is LiNi 0.94 Co 0.05 Mn 0.01 O2;

[0122] The preparation method of the precursor is as follows:

[0123] Step 1: Prepare the same metal salt mixed solution, sodium hydroxide solution, and aqueous ammonia as in Example 4. Pre-add 50 L of deionized water and 8 L of aqueous ammonia to a 100 L reactor as the base solution. Control the pH of the base solution to 12.70 (±0.10) and the ammonia concentration to 2 mol / L using sodium hydroxide solution. After completely sealing the reactor and testing its airtightness, begin introducing nitrogen (0.2 m³ / h) to completely displace the oxygen in the reactor. When the reactor temperature reaches 90°C, The metal salt mixed solution, sodium hydroxide solution and ammonia water were pumped into the reactor at a flow rate of 80mL / min, 32mL / min and 32mL / min respectively, and the stirring speed was controlled at 800r / min. The pH value of the entire reactor was maintained at 12.7 (± 0.05) and the ammonia concentration was maintained at 2.0 (± 0.05) mol / L by adjusting the flow rate of sodium hydroxide solution and ammonia water. The step-by-step feeding and nucleation were carried out for 2h (a total of 3 cycles, each nucleation was 20min, and the aging was 20min). After the reaction was completed, the alkali solution feeding was stopped to reduce the pH of the solution in the reactor to 10.80 (± 0.05). The reaction was continued for 80h. After the reaction was completed, the slurry was aged for 2h and then washed, filtered and dried in the same manner as in Example 1. LiNi was obtained. 0.94 Co 0.05 Mn 0.01 (OH)2 precursor samples, such as Figure 5 As shown, D50 is 4.9 μm, the single crystal primary particle size range is 1.2 to 1.8 μm, the single crystal morphology is polyhedron, the single crystal is a prismatic cubic polyhedron, the prism side aspect ratio is (1 to 5): 1, and the specific surface area is 2.3 m 2 / g.

[0124] Step 2: The precursor prepared in step 1 was mixed with LiOH·H2O at a lithiation ratio of 1:1.05 for 60 minutes to ensure uniform mixing. The mixture was then placed in a tube furnace and sintered at high temperature under oxygen-rich conditions. The heating rate was controlled at 3°C / min; the temperature was raised to 450°C and kept at this temperature for 4 hours, then continued to rise to 680°C and kept at this temperature for 12 hours. The mixture was then cooled naturally to room temperature, and the sample was removed and ground to obtain the single crystal positive electrode material LiNi. 0.94 Co 0.05 Mn 0.01 O2.

[0125] Currently, the sintering temperature of single crystal positive electrode materials with a nickel-cobalt-manganese ratio of 0.94:0.05:0.01 is generally 760°C. The calcination temperature in this embodiment is 680°C, which is 80°C lower than the prior art, saving energy consumption.

[0126] Comparative Example 1

[0127] This comparative example is basically the same as Example 1, with the only difference being that during the precursor preparation process, the aging process in the staged nucleation process is eliminated, and the injection of the mixed metal salt solution is directly maintained, and the pH is controlled at 12.5 (±0.05), the ammonia concentration is maintained at 2 (±0.05) mol / L, and the reaction is continued for 8 hours.

[0128] Comparative Example 2

[0129] This comparative example is basically the same as Example 1, except that in the staged nucleation step, the nucleation is continuously performed for 4 hours and the aging is performed for 4 hours without recycling.

[0130] Comparative Example 3

[0131] This comparative example is basically the same as Example 1, except that in the staged nucleation step, the pH value of the nucleation process is controlled to be 12 (±0.05).

[0132] Comparative Example 4

[0133] This comparative example is basically the same as Example 1, except that: n(Ni 2+ ):n(Co 2+ ): n(Mn 2+ )=6:3:1.

[0134] Comparative Example 5

[0135] This comparative example is basically the same as Example 4, with the only difference being that the preparation method is a conventional precursor preparation method. Specifically, during the precursor preparation process, the aging process in the staged nucleation process is eliminated, and the injection of the mixed metal salt solution is directly maintained. The pH is controlled to 12.5 (±0.05), and the ammonia concentration is maintained at 2 (±0.05) mol / L, and the reaction is continued for 8 hours.

[0136] Experimental Example 1

[0137] The SEM images of the precursors of various embodiments are prepared. The SEM images of embodiments 1 to 5 are respectively Figures 1 to 5 ,from Figures 1 to 5 It can be seen that the precursors prepared in various embodiments are uniformly dispersed primary particles, and the particles are polyhedral.

[0138] The XRD patterns of the positive electrode materials prepared in each embodiment are as follows: Figures 6 to 10 ,from Figures 6 to 10 It can be seen that the cathode material prepared in the embodiment has a typical αNaFeO 3 layered structure XRD pattern without other miscellaneous peaks, indicating that the obtained material is a single pure phase.

[0139] Take the cathode material prepared in Example 3 as an example to make a SEM image. Figure 11 As shown, from Figure 11 It can be seen that the prepared positive electrode material has no agglomeration, uniform particle size distribution and good particle dispersion.

[0140] Experimental Example 2

[0141] The positive electrode materials prepared in each embodiment and comparative example were made into button batteries, and the electrochemical properties of the positive electrode materials prepared in each embodiment and comparative example were tested.

[0142] The prepared positive electrode material samples are made into electrode plates through a series of processes, and then the plates are assembled with other required components to form button batteries. The specific steps are as follows:

[0143] First, prepare an 8wt% PVDF binder using NMP as the solvent. Then, precisely weigh the cathode material and acetylene black, which acts as a conductive agent, are mixed uniformly in a planetary ball mill. Finally, add the prepared PVDF solution to this mixture and thoroughly stir it in a ball mill again to form a uniform, viscous slurry. The cathode powder, acetylene black, and PVDF binder are mixed in a mass ratio of 80:10:10, respectively.

[0144] The electrode slurry obtained above is evenly coated on one side of the aluminum foil using a flat coater. Here, the aluminum foil serves as the current collector of the positive electrode material, and the coating thickness can be adjusted by the coater. The coated aluminum foil electrode piece is then placed on a clean glass plate and placed in a vacuum heater for drying. The dried positive electrode electrode piece is cut into a circle (φ = 13 mm). At the same time, multiple blank aluminum foil discs of the same size need to be cut out, and the mass of the blank aluminum foil is weighed and recorded. The cut electrode pieces are weighed individually and placed in the corresponding numbered positive electrode shell. At the same time, the diaphragm is cut into discs with a diameter of φ = 19 mm. The negative electrode material is selected as metallic lithium (specifications are φ = 15.8 × 1.9 mm), and the battery shell is a CR2025 button battery shell with a diameter of 20 mm and a thickness of 2.5 mm. Finally, they are transferred to the glove box for battery assembly. Battery assembly is carried out in an argon glove box (water content ≤ 1 ppm, oxygen content ≤ 1 ppm).

[0145] The electrical performance test method is as follows:

[0146] The LAND battery test cabinet was used to test the chemical properties of the button cells. The current density in the charge and discharge test is expressed as the charge and discharge rate "C". The voltage range of the battery during charge and discharge is 3.0-4.3V (vs. Li / Li + ), all electrochemical performance tests were carried out at room temperature 25℃.

[0147] The measured results are recorded in Table 1.

[0148] Table 1 Statistics of electrochemical performance of various embodiments and comparative examples

[0149]

[0150] It can be seen from Table 1 that each embodiment of the present invention has better electrochemical performance.

[0151] Comparing Comparative Example 1 with Example 1, the cycle performance of Comparative Example 1 is significantly worse than that of Example 1, indicating that the electrochemical performance of the positive electrode made from the high nickel-based precursor prepared according to the conventional preparation method is worse than that of the positive electrode made from the precursor prepared in the example of the present application;

[0152] Comparing Comparative Example 2 with Example 1, the discharge capacity, coulombic efficiency and cycle performance of Comparative Example 2 are significantly worse than those of Example 1, indicating that if the preparation method provided by the present invention is not repeated multiple times in stages, the precursor with good electrochemical performance provided by the present invention cannot be obtained;

[0153] Comparing Comparative Example 3 with Example 1, the cycle performance of Comparative Example 3 is significantly worse than that of Example 1, indicating that if the pH is not controlled in the manner of the present invention, the precursor with good electrochemical performance provided by the present invention cannot be obtained;

[0154] Comparing Comparative Example 4 with Comparative Example 5, the electrochemical performance of Comparative Example 4 was not improved compared with that of Comparative Example 5, indicating that the preparation method provided by the present invention is more suitable for preparing a precursor of a high-nickel-based positive electrode material.

[0155] In summary, the nickel-based single crystal hydroxide precursor provided in the embodiment of the present invention is a true single crystal material with a regular morphology, better size, and better dispersibility. It does not require crushing or grading after sintering to prepare the positive electrode material. The prepared positive electrode material can inherit the crystal structure of the single crystal precursor, has few defects or defect-free lithium storage structure characteristics, and has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0156] The preparation method provided by the present invention develops a new single crystal precursor preparation technology with coordinated nucleation-ripening-growth regulation. The agglomeration of amorphous nanocrystalline nuclei is greatly reduced through the staged feeding nucleation technology, and micro-nanoscale, highly dispersed, and preliminarily matured nickel-based single crystal hydroxide nuclei are prepared. The crystal growth is coordinated to achieve the controllable preparation of highly dispersed, large single crystal hydroxide precursors. The D50 of the single crystal precursor prepared by this method is controllable in the range of 1 to 5 μm, the particle size distribution is uniform, the dispersion is high, the crystal structure is controllable, the process is simple, and no additional dispersant is required. The single crystal precursor has uniform morphology, good product consistency, and can be produced on a large scale. When applied to the synthesis of single crystal positive electrode materials, it can achieve sintering preparation of true single crystal high nickel positive electrode materials under the conditions of sintering temperature <800°C and lithium over-ratio ≤5%, thus saving energy and reducing consumption from the root, and achieving green economy. The positive electrode material made from this precursor inherits the crystal structure characteristics of the single crystal precursor, has few or no defects in the lithium storage structure, and has the advantages of high specific capacity, good rate performance, and excellent reversibility.

[0157] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A nickel-based single crystal hydroxide precursor, characterized in that: The chemical formula of the precursor is Ni 1-x-y Co x Mn y (OH)2, where 0≤x≤0.2, 0≤y≤0.2, and 0≤x+y≤0.3; The precursor is a primary particle with a D50 of 1 to 5 μm, a single crystal primary particle size range of 0.2 to 2 μm, and a polyhedral morphology.

2. The nickel-based single crystal hydroxide precursor according to claim 1, characterized in that The polyhedron is a prismatic cubic polyhedron, the aspect ratio of the prism side is (1-5):1, and the specific surface area is less than 10m 2 / g.

3. A method for preparing a precursor according to claim 1, characterized in that: include: Stepwise nucleation: Nucleation: The mixed metal salt solution, alkaline solution and ammonia water are introduced into the reactor in parallel, the pH of the reactor is controlled at 12.5-13.0, and the ammonia concentration is maintained at 1.5-2.5 mol / L for 20-60 minutes; Maturation: Stop feeding the mixed metal salt solution, alkali solution and ammonia solution, and keep it for 20 to 60 minutes; The nucleation-ripening step is repeated 3 to 10 times to complete the staged nucleation; Growth: Stop feeding the mixed metal salt solution, adjust the alkaline solution and ammonia solution feed to make the solution pH 10.5-11.5, and maintain the ammonia concentration at 1.5-2.5 mol / L. Keep it for 20-100 hours until the target particle size is reached, then stop all feeding; The slurry is aged for 0.5 to 2 hours; The temperature of the entire reaction process is 60-90°C.

4. The preparation method according to claim 3, characterized in that Includes at least one of the following features (1) to (4): (1) The bottom liquid in the reactor accounts for 50-60% of the reactor volume, the ammonia concentration in the bottom liquid is 1.5-2.5 mol / L, and the pH value is 12.5-13.0; (2) The concentration of metal ions in the mixed metal salt solution is 1 to 2 mol / L, and during the nucleation process, the injection flow rate of the mixed metal salt solution is 10 mL / min to 2 L / min; (3) After the aging is completed, the precipitate is extracted from the slurry, washed with an alkaline solution at a temperature of 60 to 90° C. and deionized water in sequence until the pH value of the precipitate is lower than 10, and then dried to obtain a precursor; (4) The concentration of the ammonia water is 10-14 mol / L; the alkaline solution is a sodium hydroxide solution with a concentration of 8-10 mol / L.

5. The preparation method according to claim 3, characterized in that The flow rate of ammonia solution is 5 mL / min to 1 L / min, and the flow rate of sodium hydroxide solution is 5 mL / min to 1 L / min.

6. A method for preparing a positive electrode material, characterized in that: The method comprises mixing and sintering a lithium source with the precursor according to claim 1 or 2 or a precursor prepared by the preparation method according to any one of claims 3 to 5, wherein the molar ratio of lithium in the lithium source to the metal in the precursor is 1:1.01 to 1.

05.

7. The preparation method according to claim 6, characterized in that The sintering conditions are: keeping the temperature at 400-500°C for 2-6 hours in an oxygen atmosphere, then heating to 680-750°C and keeping the temperature for 8-15 hours.

8. A positive electrode material, characterized in that The product is prepared by the preparation method according to claim 6 or 7.

9. A positive electrode, characterized in that Comprising the positive electrode material as claimed in claim 8.

10. A battery, characterized in that: Comprising the positive electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Preparing method of large-granularity single-crystal lithium ion battery three-element positive electrode material

    CN109286016A

  • Method for preparing high-nickel ternary single crystal material precursor through coprecipitation method

    CN114436346A

  • A method for preparing single crystal high nickel positive electrode material

    CN115028210B

  • High-nickel type lithium nickel cobalt manganese oxide single crystal precursor and preparation method thereof, and high-nickel type lithium nickel cobalt manganese oxide single crystal cathode material

    CN110048118A

  • Methods for preparing nickel-cobalt-manganese ternary positive electrode material with large single crystal morphology and precursor thereof

    CN111943279A

Cited By

  • Monocrystal nickel-rich cobalt-free positive electrode precursor material as well as preparation method and application thereof

    CN121627081A